The Impact of Product Visualization and Emotional Triggers on Impulse Buying: Moderating Role of Previous Experience in E-Commerce Among Generation Z Consumers - Ainurrafiq, Azka Hafiyan; Ainurrafik, Rinrin (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the effect of product visualization and emotional triggers on impulse purchase decisions in e-commerce and to examine the role of previous experience as a moderating variable among Generation Z consumers. This research uses a quantitative survey method. A closed questionnaire with a semantic differential scale was given to 205 respondents consisting of active users of e-commerce platforms aged at least 18 years old and who have made impulse buying in the last three months. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS version 24. The results showed that product visualization and emotional triggers influence impulse purchase decisions. In addition, previous experience acts as a moderating variable that strengthens the relationship between product visualization and impulse buying. This study provides new insights into e-commerce consumer behavior in the digital era, especially among Generation Z. The implication is that marketers can design more effective visual and emotional strategies to encourage impulse buying and ensure a positive consumer experience to increase loyalty. Keywords : Product Visualization, Emotional Trigger, Impulse Buying, Previous Experience, Generation Z